Gendered Issues and Voices in Public Discourses on Industrial Development in Northern Norway - Kvidal-Røvik, Trine (The Rural Development Insitute (RDI), Brandon University, 2018)
Source at https://journals.brandonu.ca/jrcd/index . This article deals with gender and industrial developments in the northernmost part of Norway, where there are growing opportunities within the mining, oil and gas industries. Large companies move into the region for shorter or longer periods of time, leading to restructuring and change in these rural areas. These industries are typically male-dominated, and many of the workers coming to the region as part of such developments are men. The purpose of the study is to examine local public discourses on industry development in Northern Norway during a time of industrial restructuring. Using approaches from media studies and discourse analysis, I examine local public discourses to see to what extent they are ‘gender conscious’ in that they present concerns regarding gendered consequences of industrial restructuring processes, and also to see who speaks—in terms of gender—on the issues brought forth. I find that gendered issues linked to industrial restructurings in Northern Norway are not addressed in the public discourses and also that men, to a higher degree than women, speak on issues of industry development. Overall, gender does not seem to be a relevant topic, and with this, issues of gender are symbolically defined as irrelevant to understandings of industry development. I claim the invisibility of gender issues and the imbalance of men’s and women’s voices (re)produces a lack of awareness of gender in industry development and is part of creating an understanding of Northern Norway as a place where men are a better fit for industry developments than women.